Study on the enhancement of thixotropic properties of steel slag-based digital concrete by metakaolin - Lingli Zhu; Zhenkun Zhao; Yu Zhao; Yun Xiang; Xuemao Guan (Case Studies in Construction Materials)
To improve the utilization rate of waste steel slag, metakaolin was preferably selected as a thixotropic enhancer to prepare a high-thixotropic steel slag-based digital concrete slurry applicable to the digital concrete process. The changes in dynamic and static yield stresses and plastic viscosity of the steel slag-based digital concrete slurry after adding metakaolin were studied. Meanwhile, the influence of metakaolin on the thixotropy of the slurry was investigated from both the viscous and elastic aspects. Moreover, the dynamic yield stress and plastic viscosity were fitted with the thixotropy test results to explore the internal relationship among them. The experimental results showed that as the metakaolin content increased (0 %, 1 %, 2 %, 3 %, 4 %), the dynamic and static yield stresses and plastic viscosity of the slurry first increased and then decreased, reaching the maximum value when the content was 2 %. After adding metakaolin, the viscous thixotropy of the slurry was improved, and it was the best when the content was 2 %. In terms of elastic thixotropy, the improvement effect was the best when the content was 2 %, while a 3 % metakaolin content damaged the elastic thixotropy of the slurry. The plastic viscosity of the slurry had a relatively strong correlation with viscous thixotropy but a poor correlation with elastic thixotropy. It was known from the microscopic tests that metakaolin provided nucleation sites for the slurry, increased the hydration reaction rate of the slurry, reduced the internal pores of the slurry, made the flocculation structure denser, and simultaneously promoted the formation of ettringite. Therefore, the thixotropy of the slurry was enhanced, which played an important role in the application of steel slag in the digital concrete field.